Attitudes toward menopause, sexual function and depressive symptoms in Mexican women. (3rd April 2018) - Marván, Ma. Luisa; Espinosa-Hernández, Graciela; Martínez-Garduño, Maria Dolores; Jasso, Kristian
Abstract: The objective of this study was to explore the beliefs and attitudes toward menopause, depressive symptoms and sexual function in both premenopausal and postmenopausal Mexican women. The Beliefs about and Attitudes toward Menopause Questionnaire, the Female Sexual Function Index and the Center for Epidemiologic Studies Depression Scale were answered by 253 women between the ages of 46 and 59 years. Negative attitudes toward menopause were associated with a more depressive symptomatology, but there was no association between positive attitudes and depressive symptomatology. Among sexually active women (92% premenopausal and 70% postmenopausal), positive attitudes were associated with better sexual function, while negative attitudes were associated with worse sexual function. Our findings suggest that besides biological factors, psychosocial factors may also play an important role in middle-aged women's sexual functioning and in their psychological adjustment.